2010
DOI: 10.1111/j.1743-6109.2009.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality During Pregnancy

Abstract: Introduction Sexuality is an important part of health and well-being. Sexual behavior modifies as pregnancy progresses, influenced by biological, psychological, and social factors. Aim To evaluate changes in sexual perceptions and activities during pregnancy and to determine sexual dysfunctions in that period. Main Outcome Measures Sexual perceptions (desire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
2
35

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(199 citation statements)
references
References 34 publications
16
146
2
35
Order By: Relevance
“…Apesar de diversos trabalhos analisarem a função sexual durante a gravidez 3,4,[7][8][9][10][11]19,25 , não encontramos estudos que a correlacionassem com a qualidade de vida em gestantes saudáveis. Sabe-se que a função sexual passa por mudanças na gestação, ocorrendo o aumento de sintomas de disfunção sexual, como a diminuição de desejo e a dispareunia nesse período 9,[11][12][13] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Apesar de diversos trabalhos analisarem a função sexual durante a gravidez 3,4,[7][8][9][10][11]19,25 , não encontramos estudos que a correlacionassem com a qualidade de vida em gestantes saudáveis. Sabe-se que a função sexual passa por mudanças na gestação, ocorrendo o aumento de sintomas de disfunção sexual, como a diminuição de desejo e a dispareunia nesse período 9,[11][12][13] .…”
Section: Discussionunclassified
“…Somente o fato de tomar conhecimento da gravidez, logo nas primeiras semanas, parece afetar a atividade sexual feminina, diminuindo o número de coitos 2 . Estudos mostram que nos mais diversos contextos socioeconômico e cultural as mulheres podem apresentar dificuldades com desejo, excitação, orgasmo, lubrificação, além de insatisfação sexual e dispareunia na gravidez [2][3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionunclassified
“…As for sexuality, this is one of the most natural characteristics of being human (6) . In this study there was one woman who reported having increased sexual activity towards the end of pregnancy; compatible to the acknowledged sexual desire due to increased libido in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Literature denotes that sexuality is one of the most natural characteristics of being human (6) ; it is a biological, physiological reality and one of the engines of human existence.…”
Section: Embarazo Estilo De Vida Cambio Parto Introductionmentioning
confidence: 99%
“…Pregnancy is characterized by biochemical, functional, anatomical and emotional changes that start at a very early stage and remain in its course. All these changes interfere directly or indirectly, in the sexual behavior of pregnant women, in different levels and form (1,10,(26)(27)(28) . Thus, the transition to parenthood can be understood as a phase of the potential psychosocial crisis and a critical period when most couples experience changes in their usual pattern of sexual behavior (29) .…”
Section: Introductionmentioning
confidence: 99%